Powder coating method and finished powder and finished magnetic powder core preparation method
Through the use of ultrasonic adhesion inorganic powder during the insulation covering process of the amorphous magnetic powder and reacting in the alkaline solution to form the insulating coating layer, the problem of high cost, serious environmental pollution and low magnetic performance in existing technology have been solved. Higher magnetic guidance and lower losses.
Patent Information
- Application Number
- CN202210644501.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-11-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2039-11-25
AI Technical Summary
The prior art has high cost, serious environmental pollution, uneven coating and excessive local exothermic powder particles in the insulating coating process of amorphous magnetic powder core, resulting in changes in the amorphous structure of the powder particles on the surface, thereby reducing magnetic permeability and improving Issues of hysteresis loss.
The inorganic powder is mixed and attached to the alloy powder using ultrasonic waves, and then fully reacted and dried in an alkaline solution to form an insulating coating layer and obtain the coated powder. This method does not require acidic solutions and avoids the cost and environmental problems caused by corrosive reactions.
The non -crystal structure changes caused by uneven coverage and excessive parts of the powder particles are effectively avoided, and the magnetic guidance rate and magnetic performance of the magnetic powder core are improved, and the production cost and environmental pollution are reduced.
Smart Images

Figure BDA0003683544320000051 
Figure BDA0003683544320000061 
Figure BDA0003683544320000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soft magnetic alloy metallurgy, and in particular to a powder coating method and a method for preparing finished powder and finished magnetic powder core. Background Art
[0002] Amorphous materials have high saturation magnetic induction, high magnetic permeability, low coercive force and low high-frequency loss, good hardness, wear resistance and corrosion resistance, good temperature and environmental stability, etc. Their excellent comprehensive performance replaces Permalloy, silicon steel and ferrite, and is used in power electronics technology, showing the characteristics of small size, high efficiency and energy saving. It has the best performance-price ratio among all metal soft magnetic materials.
[0003] Insulation coating is a key technology in the preparation process of amorphous magnetic powder cores. The performance of the insulation coating layer is an important factor affecting the high-frequency loss of the magnetic powder core. If the insulation coating layer is incomplete or damaged, the eddy current loss between the magnetic powder particles will increase sharply, thereby increasing the high-frequency loss of the magnetic powder core.
[0004] In the existing technology application, the insulation coating process usually uses acidic solution for corrosive insulation coating treatment, and the acidic solution is usually diluted by volatile organic matter, which causes cost increase and environmental damage; and the corrosion process reaction control is difficult, and it is easy to cause uneven coating and excessive local heat release of powder particles, resulting in changes in the amorphous structure of the powder particle surface. At the same time, the corrosion of powder particles will cause the adverse consequences of decreased powder magnetic permeability and increased hysteresis loss. Summary of the invention
[0005] The present invention provides a powder coating method to overcome the deficiencies of the prior art.
[0006] The powder coating method comprises the following steps: S1, preparing an amorphous alloy powder, wherein the alloy components of the alloy powder include FeSiBCMN series amorphous alloy, wherein M is any one of Ni and Mo elements, and N is any one of Cr and Mn elements; S2, mixing inorganic powder with ultrasound and attaching it to the alloy powder to obtain attached powder; S3, mixing an alkaline solution with the attached powder and allowing them to react fully, and drying the mixture to form an insulating coating layer on the surface of the attached powder to obtain coated powder.
[0007] Furthermore, in step S1, the mesh ratio of the alloy powder is: -100 mesh to +150 mesh accounts for 10-40%, -150 mesh to +200 mesh accounts for 20-70%, and -200 mesh to +400 mesh accounts for 10-30%; the mesh number of the inorganic powder is set to be above 8000 mesh.
[0008] Furthermore, the inorganic powder includes SiO 2The alkaline solution is a NaOH solution. In step S3, the reaction formula of the inorganic powder and the alkaline solution is: SiO 2 +2NaOH=Na 2 SiO 3 +H 2 O.
[0009] Furthermore, in step S3, a binder is added to the attached powder after sufficient reaction with the alkaline solution to stir until it is uniformly dried.
[0010] Furthermore, the binder is an inorganic binder or an organic binder.
[0011] Furthermore, the adhesive is silicone resin, water glass or epoxy resin, and the added amount of the adhesive is 0.2-2.5%.
[0012] Furthermore, in step S1, the alloy composition of the alloy powder is Fe (100-x-y-z-a-b) Si x B y C z M a N b , where M is any one of Ni and Mo elements, and N is any one of Cr and Mn elements; where 6﹤x﹤11, 9﹤y﹤16, 1﹤z﹤8, 0≤a﹤5, 0﹤b﹤5.
[0013] Furthermore, the alloy components of the alloy powder include Fe 76 Si 7.5 B 7 C 4 Ni 1.5 Cr 3 The performance of the amorphous strip prepared with this composition is shown in that the Bs is 1.54T, the Hc is 1.7A / m, and the μi@1k,0.5V is 21400;
[0014] or its composition includes Fe 75 Si 8 B 7 C 4 Mo 1 Cr 5 The performance of the amorphous ribbon prepared with this composition is shown in that the Bs is 1.33T, the Hc is 1.2A / m, and the μi@1k,0.5V is 38600;
[0015] or its composition includes Fe 78 Si 6 B 8 C 3 Ni 3 Mn 2The performance of the amorphous strip prepared with this composition is shown in that the Bs is 1.71T, the Hc is 3.6A / m, and the μi@1k,0.5V is 8400;
[0016] or its composition includes Fe 76 Si 9 B 7 C 5 Cr 3 The performance of the amorphous strip prepared with this composition is shown in that the Bs is 1.42T, the Hc is 1.5A / m, and the μi@1k,0.5V is 28500;
[0017] or its composition includes Fe 78 Si 6 B 9 C 4 Cr 3 The performance of the amorphous strip prepared with this composition is shown in that the Bs is 1.51T, the Hc is 2.2A / m, and the μi@1k,0.5V is 13600.
[0018] The method for preparing the finished powder is applied by the above-mentioned powder coating method, which also includes the following steps:
[0019] S4. Add a lubricant to the obtained coated powder, and stir and mix it with a stirrer to obtain a finished powder.
[0020] The method for preparing a finished magnetic powder core uses the method for preparing a finished powder core as described above, and further includes the following steps:
[0021] S5, treating, sintering, annealing and curing the obtained finished powder to obtain a magnetic powder core base block;
[0022] S6. Performing surface coating treatment on the magnetic powder core base block to obtain a finished magnetic powder core.
[0023] The beneficial effects of the present invention are:
[0024] The corresponding powder insulation coating application is carried out by adopting a non-corrosive treatment method to effectively improve the cost and environmental pollution problems. It does not require an acidic solution for a corresponding corrosive reaction, and can effectively avoid changes in the amorphous structure of the powder surface caused by uneven coating and excessive local heat release of the powder, and avoid the decrease in the magnetic permeability of the amorphous powder and the deterioration of other magnetic properties. DETAILED DESCRIPTION
[0025] In order to make the technical solution, purpose and advantages of the present invention more clearly understood, the present invention is further explained with reference to the following embodiments.
[0026] A method for preparing an amorphous magnetic powder core specifically involves the following steps:
[0027] S1. Smelting the alloy raw materials in a smelting furnace to prepare a master alloy;
[0028] S2, preparing corresponding amorphous powder using the master alloy;
[0029] S3, mixing the amorphous powder in a proportion to obtain an amorphous mixed powder;
[0030] S4, subjecting the amorphous mixed powder to an insulation coating treatment to obtain an amorphous coated powder;
[0031] S5, adding a lubricant to the amorphous coated powder, and stirring and mixing to obtain an amorphous finished powder;
[0032] S6, performing pressing, sintering, annealing and curing on the amorphous finished powder to obtain a magnetic powder core base block;
[0033] S7, performing surface coating treatment on the magnetic powder core base block to obtain an amorphous magnetic powder core.
[0034] In step S1, the present invention provides a master alloy for an iron-based amorphous alloy, the composition of which is expressed as Fe (100-x-y-z-a-b) Si x B y C z M a N b , where M is any one of Ni and Mo elements, and N is any one of Cr and Mn elements; where 6﹤x﹤11, 9﹤y﹤16, 1﹤z﹤8, 0≤a﹤5, 0﹤b﹤5.
[0035] The master alloy for the iron-based amorphous alloy can be based on Fe 78 Si 9 B 13 , which is made by adding elements to change the atomic arrangement inside the amorphous alloy.
[0036] Specifically, in response to the preparation needs, by 78 Si 9 B 13 On the basis of the composition, elements such as C, Ni, Mo, Cr, and Mn are added and substituted to design the alloy composition; the weight ratio of each required element is calculated according to the designed atomic ratio of the composition, and then the weight of each raw material required for each added element is calculated; and then the weight of each required raw material is calculated and smelted to prepare the master alloy for the iron-based amorphous alloy.
[0037] Embodiment 1:
[0038] The chemical composition expression of the master alloy for the iron-based amorphous alloy is Fe 76 Si 7.5 B 7 C 4 Ni 1.5 Cr 3 The corresponding amorphous powder is prepared from the master alloy, and then after conventional powder mixing, conventional insulation coating treatment, pressing treatment, sintering treatment, annealing treatment, curing treatment and surface coating treatment, the corresponding magnetic powder core can be prepared.
[0039] Specifically, the powder ratio is 10% for 100-150 mesh, 50% for 150-200 mesh, 30% for 200-270 mesh, and 10% for 270-400 mesh. The magnetic permeability of the prepared magnetic powder core is 60, the DC bias magnetic capacity is 55%, and the loss is 310mw / cm3@50k,100mT.
[0040] Embodiment 2:
[0041] The chemical composition expression of the master alloy for the iron-based amorphous alloy is Fe 75 Si 8 B 7 C 4 Mo 1 Cr 5 The corresponding amorphous powder is prepared from the master alloy, and then after conventional powder mixing, conventional insulation coating treatment, pressing treatment, sintering treatment, annealing treatment, curing treatment and surface coating treatment, the corresponding magnetic powder core can be prepared.
[0042] Specifically, the powder ratio is 10% for 100-150 mesh, 50% for 150-200 mesh, 30% for 200-270 mesh, and 10% for 270-400 mesh. The magnetic permeability of the prepared magnetic powder core is 60, the DC bias magnetic capacity is 51%, and the loss is 186mw / cm3@50k, 100mT.
[0043] Embodiment 3:
[0044] The chemical composition expression of the master alloy for the iron-based amorphous alloy is Fe 78 Si 6 B 8 C 3 Ni 3 Mn 2 The corresponding amorphous powder is prepared from the master alloy, and then after conventional powder mixing, conventional insulation coating treatment, pressing treatment, sintering treatment, annealing treatment, curing treatment and surface coating treatment, the corresponding magnetic powder core can be prepared.
[0045] Specifically, the powder ratio is 10% for 100-150 mesh, 50% for 150-200 mesh, 30% for 200-270 mesh, and 10% for 270-400 mesh. The magnetic permeability of the prepared magnetic powder core is 60, the DC bias magnetic capacity is 64%; the loss is 362mw / cm3@50k,100mT.
[0046] Embodiment 4:
[0047] The chemical composition expression of the master alloy for the iron-based amorphous alloy is Fe 76 Si 9 B 7 C 5 Cr 3 The corresponding amorphous powder is prepared from the master alloy, and then after conventional powder mixing, conventional insulation coating treatment, pressing treatment, sintering treatment, annealing treatment, curing treatment and surface coating treatment, the corresponding magnetic powder core can be prepared.
[0048] Specifically, the powder ratio is 10% for 100-150 mesh, 50% for 150-200 mesh, 30% for 200-270 mesh, and 10% for 270-400 mesh. The magnetic permeability of the prepared magnetic powder core is 60, the DC bias magnetic capacity is 54%, and the loss is 280mw / cm3@50k,100mT.
[0049] Embodiment 5:
[0050] The chemical composition expression of the master alloy for the iron-based amorphous alloy is Fe 78 Si 6 B 9 C 4 Cr 3 The corresponding amorphous powder is prepared from the master alloy, and then after conventional powder mixing, conventional insulation coating treatment, pressing treatment, sintering treatment, annealing treatment, curing treatment and surface coating treatment, the corresponding magnetic powder core can be prepared.
[0051] Specifically, the powder ratio is 10% for 100-150 mesh, 50% for 150-200 mesh, 30% for 200-270 mesh, and 10% for 270-400 mesh. The magnetic permeability of the prepared magnetic powder core is 60, the DC bias magnetic capacity is 56%, and the loss is 275mw / cm3@50k, 100mT.
[0052] Generally speaking, the performance of amorphous alloys is usually reflected by the performance of amorphous strips. The performance of the corresponding amorphous strips prepared by the corresponding iron-based amorphous alloy master alloy is as follows:
[0053] Alloy composition Bs(T) Hc(A / m) μi@1k,0.5V <![CDATA[Fe 76 If 7.5 B 7 C 4 of 1.5 Cr 3 ]]> 1.54 1.7 21400 <![CDATA[Fe 75 Si 8 B 7 C 4 Mon 1 Cr 5 ]]> 1.33 1.2 38600 <![CDATA[Fe 78 Si 6 B 8 C 3 Ni 3 Mr 2 ]]> 1.71 3.6 8400 <![CDATA[Fe 76 Si 9 B 7 C 5 Cr 3 ]]> 1.42 1.5 28500 <![CDATA[Fe 78 Si 6 B 9 C 4 Cr 3 ]]> 1.51 2.2 13600
[0054] Embodiment 6:
[0055] In step S2, the master alloy is further subjected to a rapid cooling method to prepare the corresponding amorphous powder. The rapid cooling method can adopt a rapid cooling amorphous preparation method of the prior art including: single-roller rapid quenching method, double-roller rapid quenching method, water atomization method, gas atomization method, water-gas atomization combined method, etc.
[0056] The master alloy can be used to prepare a corresponding amorphous strip by the single-roller rapid quenching method or the double-roller rapid quenching method, and the prepared amorphous strip is mechanically crushed to prepare a corresponding flaky first amorphous powder.
[0057] The master alloy can be used to prepare a corresponding spherical second amorphous powder by the water atomization method, gas atomization method, or water-gas atomization combined method.
[0058] In the step S2, it includes the following steps:
[0059] S2-1, preparing a first amorphous powder in a flaky state by using the master alloy for the iron-based amorphous alloy;
[0060] S2-2. A second amorphous powder in a spherical state is prepared using the mother alloy for the iron-based amorphous alloy.
[0061] In step S3, the present invention mixes the first amorphous powder and the second amorphous powder in a certain ratio to obtain an amorphous mixed powder. The mixing method of the amorphous mixed powder is selected as follows:
[0062] The mesh number range of the first amorphous powder is -100 to +270 mesh, and the mesh number range of the second amorphous powder is -200 to +400 mesh. -100 mesh to +150 mesh accounts for 10 to 30%, -150 mesh to +200 mesh accounts for 20 to 50%, -200 mesh to +270 mesh accounts for 10 to 30%; the proportion of the second amorphous powder is 10 to 40%. The above-mentioned adjustment of the proportion of the first amorphous powder and the second amorphous powder with different mesh numbers is mixed to obtain the amorphous mixed powder with good fluidity. The main parameters of good powder fluidity are: loose density, tap density, angle of repose, dispersion, etc.; the comprehensive index is the fluidity index, which can be tested using the Dandong Better Powder Properties Analyzer; the fluidity index is above 70 for a good level, and the larger the fluidity index, the better the fluidity; the powder with good fluidity has less resistance between powder particles during the molding process, which is conducive to molding; under the same pressure conditions, the density of the magnetic powder core made of it can be larger and the product performance is better.
[0063] By mixing and applying the first amorphous powder and the second amorphous powder of different morphology types, the fluidity and molding density of the powder are effectively improved, thereby improving the DC bias capability of the amorphous magnetic powder core prepared using the powder.
[0064] Using the same production conditions, the prepared product performance is as follows: the prepared improved magnetic powder core product has higher magnetic permeability, lower loss, and is more conducive to product miniaturization and high-frequency application requirements.
[0065]
[0066] Embodiment 7:
[0067] In step S4, a first insulation coating method is applied to perform insulation coating treatment on the amorphous mixed powder, and the first insulation coating method includes the following steps:
[0068] S4-01, mixing the inorganic powder with ultrasound and attaching it to the amorphous mixed powder to obtain amorphous attached powder;
[0069] S4-02, mixing the alkaline solution with the amorphous attached powder and reacting them fully, drying and fixing them with a binder, so that an insulating coating layer is fixedly formed on the surface of the amorphous attached powder, and the amorphous coated powder is obtained.
[0070] The inorganic powder is SiO 2 or Fe 2 O 3 The inorganic oxides; the mesh number of the inorganic powder is above 8000 meshes, achieving an ultra-fine effect, and the particles thereof approach the nanometer level.
[0071] Specifically, the amorphous mixed powders of the above-mentioned mesh sizes are prepared and mixed evenly with a V-type blender. At the same time, an ultrasonic vibrator is used in the V-type blender during the mixing and stirring of the amorphous mixed powder to output ultrasonic waves. Based on the fact that the ultrafine inorganic powder itself has a certain adsorption capacity, the inorganic powder is evenly attached to the amorphous mixed powder to obtain amorphous adhered powder.
[0072] The alkaline solution is mixed with the amorphous attached powder and fully reacted. The alkaline solution can be selected as a NaOH solution. In the above reaction process, the chemical reaction formula may be involved: SiO 2 +2NaOH=Na 2 SiO 3 +H 2 O, room temperature conditions, stirring evenly to fully react; adding a binder to the amorphous attached powder after fully reacting with the alkali solution to stir until uniformly dried, so that the surface of the amorphous attached powder forms a layer with Na 2SiO 3 An insulating coating layer is formed to obtain an amorphous coated powder.
[0073] The binder is an inorganic or organic binder with adhesive properties; the binder is silicone resin, water glass or epoxy resin, and the addition amount of the binder is 0.2-2.5%.
[0074] The inorganic powder can be added in an amount according to the required content of forming a single-layer insulating coating layer, and the amount of inorganic powder added can be increased according to performance requirements, so that the thickness of the obtained attached insulating coating layer approaches that of a single layer, and is close to complete attachment.
[0075] The application of the first insulating coating method adopts a non-corrosive treatment method for the corresponding insulating coating application to effectively improve cost issues and environmental pollution issues. It does not require an acidic solution for a corresponding corrosive reaction, and can effectively avoid changes in the amorphous structure of the powder surface due to uneven coating and excessive local heat release of the powder, thereby avoiding a decrease in the magnetic permeability of the amorphous finished powder and deterioration of other magnetic properties.
[0076] Using the same production conditions, the prepared product performance is as follows: the prepared improved magnetic powder core product has higher magnetic permeability, lower loss, and is more conducive to product miniaturization and high-frequency application requirements.
[0077]
[0078] Embodiment 8:
[0079] Based on the fact that the first and / or second amorphous powder is prepared by applying the master alloy for the iron-based amorphous alloy containing Fe and Si; in step S4, a second insulation coating method is applied to perform insulation coating treatment, and the second insulation coating method includes the following steps:
[0080] S4-11, preheating the rotary kiln to 240-450° C., and adding the amorphous mixed powder into the rotary kiln;
[0081] S4-12. Oxygen-containing air is continuously introduced into the rotary kiln. The amorphous mixed powder is turned over in the rotary kiln to allow the surface of the amorphous mixed powder to fully react with the oxygen-containing air, so that an insulating coating layer is fixedly formed on the surface of the amorphous mixed powder to obtain the amorphous coated powder.
[0082] Specifically, the obtained amorphous mixed powder is baked in a rotary kiln to perform stress relief annealing; the rotary kiln is provided with a corresponding oxygen supply mechanism and a turning mechanism, so that oxygen-containing air is continuously supplied to the rotary kiln by the oxygen supply mechanism, and the amorphous mixed powder in the kiln is turned over by the turning mechanism, so that the surface of the amorphous mixed powder reacts fully with the oxygen-containing air, and the chemical reaction formula involves: Fe+O 2 =Fe 2 O 3 and Si+O 2 =SiO 2 , turn over and stir evenly to fully react; so that an insulating coating layer with corresponding oxides is formed on the surface of the amorphous mixed powder to obtain coated powder.
[0083] The application of the second insulation coating method effectively improves production costs and environmental pollution problems by using hot air to generate the insulation coating layer in its insulation coating step; at the same time, it can effectively improve the quality of the insulation coating layer; and reduce the influence of the introduction of foreign matter in its insulation coating process on the magnetic properties of the prepared amorphous magnetic powder core.
[0084] Using the same production conditions, the prepared product performance is as follows: the prepared improved magnetic powder core product has higher magnetic permeability, lower loss, and is more conducive to product miniaturization and high-frequency application requirements.
[0085]
[0086] Embodiment 9:
[0087] In step S4, a third insulation coating method is applied to perform insulation coating treatment, and the third insulation coating method includes the following steps:
[0088] S4-21. Add an inorganic adhesive to the amorphous mixed powder and mix them evenly so that an insulating coating layer is fixedly formed on the surface of the amorphous mixed powder to obtain the amorphous coated powder.
[0089] The obtained amorphous mixed powder is added into a double-shaft mixer, and an adhesive inorganic substance is added and stirred until uniform, so that an insulating coating layer is formed on the surface of the amorphous mixed powder to obtain an amorphous coated powder; the adhesive inorganic substance used is a sodium silicate solution or an inorganic silicone resin, preferably a sodium silicate solution, the modulus of the sodium silicate solution is preferably 2.5-3.5, and the Baume degree is preferably 0.35-0.48. The proportion of the sodium silicate solution used is 0.5-3.2%, and it is diluted with a diluent, and the proportion of the diluent is 1.2-6.5%. The diluent selection may include but is not limited to water, acetone, and ethanol.
[0090] The application of the third insulating coating method, through the use of adhesive inorganic substances to coat the amorphous mixed powder, acts as a binder and also as an insulating coating agent, effectively improving production efficiency and reducing the introduction of non-magnetic materials, thereby improving the magnetic permeability of the product and optimizing the magnetic properties of the product.
[0091] In step S5, the lubricant used in the above embodiment includes but is not limited to zinc stearate, paraffin wax, and barium stearate.
[0092] Using the same production conditions, the prepared product performance is as follows: the prepared improved magnetic powder core product has higher magnetic permeability, lower loss, and is more conducive to product miniaturization and high-frequency application requirements.
[0093]
[0094] Embodiment 10:
[0095] In the present invention, a method for treating a surface coating of an amorphous product is applied, which comprises the following steps:
[0096] (1) performing surface pretreatment on the amorphous product so that a pretreated insulating layer is formed on the surface of the amorphous product;
[0097] (2) The amorphous product after surface pretreatment is subjected to preheating treatment at a temperature of 180 to 240° C.; then, a second insulating material is roll-coated; the amorphous product after the preheating treatment absorbs and melts the second insulating material with its own heat, so that a roll-coated coating is formed on the pretreated insulating layer.
[0098] The second insulating material is acetal insulating powder, phenolic insulating powder or epoxy insulating powder.
[0099] The thickness of the pre-treated insulating layer ranges from 20 to 150 μm, preferably from 30 to 80 μm; the thickness of the roll-coated coating ranges from 100 to 400 μm, preferably from 150 to 250 μm.
[0100] Wherein, in the above step (1), the following steps are included:
[0101] (1-01), heating the amorphous product to a temperature of 150 to 250° C.;
[0102] (1-02) The amorphous product after heating is subjected to electrostatic spraying treatment with a first insulating powder by using an electrostatic spraying device, so that the pre-treated insulating layer is formed on the surface of the amorphous product; the first insulating powder is acetal insulating powder, phenolic insulating powder or epoxy insulating powder.
[0103] Embodiment 11:
[0104] The difference between this embodiment and the above-mentioned embodiment 10 is that in step (1), it includes the following steps:
[0105] (1-11), spraying the amorphous product with a first insulating paint using a liquid spray gun; the first insulating paint is acetal insulating paint, phenolic insulating paint or epoxy insulating paint;
[0106] (1-21) The amorphous product after the spraying treatment is baked and heated, and the baking temperature is 100-150° C., so that the pre-treated insulating layer is formed on the surface of the amorphous product.
[0107] Specifically, the application principle of the surface coating treatment method of amorphous products of the present invention is as follows:
[0108] First, the amorphous product is subjected to surface pretreatment with a first insulating powder or a first insulating paint, so that a thin pre-treated insulating layer is formed on the rough surface of the amorphous product, thereby improving the insulation of the amorphous product and compensating for the surface defects of the amorphous product (such as residual holes) to a certain extent; and then the amorphous product is subjected to roll coating with a second insulating material. Based on the premise that the amorphous product itself has been preheated, the second insulating material in the material box can be adsorbed by the heated amorphous product by roll coating to form a roll coating.
[0109] During the roll coating process, the amorphous product is in a rolling state in the material box. By adjusting the parameters and process of the roll coating equipment to control the rolling speed of the amorphous product, the uniformity of the roll coating formation can be effectively controlled; the second insulating material is concentrated in a material box, so that the second insulating material in the roll coating process is concentrated and not dispersed, and the roll coating process basically does not consume the second insulating material extra, thereby realizing the saving of raw materials.
[0110] Compared with the prior art of directly applying spraying or rolling coating to treat the surface of amorphous products with insulating coating, this solution is based on the step-by-step processing application of a double-layer insulating coating. By adjusting the matching of rolling coating equipment parameters, the thickness and uniformity of the insulating coating are controlled, and the surface quality of the insulating coating is improved.
[0111] Based on the application of the surface coating treatment method of the amorphous product, the qualified rate of the amorphous product spraying is effectively improved and the surface quality of its insulating coating is improved; at the same time, the uniformity of the thickness of its insulating coating can be ensured, and the coating material can be saved.
[0112] Then, in step S7, the above-mentioned surface coating treatment method for an amorphous product may be applied to perform surface coating treatment on the magnetic powder core base block.
[0113] Embodiment 12:
[0114] Based on the application of the prior art, the iron-based amorphous alloy master alloy of the present invention can also be processed and prepared into a corresponding magnetic core, and the processing steps are as follows:
[0115] [1] A corresponding amorphous strip is prepared using the master alloy for the iron-based amorphous alloy;
[0116] [2] Winding or stacking the amorphous strip and annealing it to obtain a magnetic core matrix;
[0117] [3] Performing surface coating treatment on the magnetic core substrate.
[0118] Embodiment 13:
[0119] The magnetic core substrate prepared in step [2] of Example 12 may be subjected to surface coating treatment using the amorphous product surface coating treatment method described in Example 10 or 11 above.
[0120] The above description is only a preferred embodiment of the present invention. Those skilled in the art can still modify the embodiment without departing from the implementation principle of the present invention, and the corresponding modified scheme should also be regarded as the protection scope of the present invention.
Claims
1. A powder coating method, characterized in that: The following steps are involved: S1. preparing an amorphous alloy powder, wherein the alloy composition of the alloy powder includes an FeSiBCMN series amorphous alloy, wherein M is any one of Ni and Mo elements, and N is any one of Cr and Mn elements; S2, mixing the inorganic powder with ultrasound and attaching it to the alloy powder to obtain attached powder; S3, mixing the alkaline solution with the attached powder and reacting them fully, and drying them so that an insulating coating layer is formed on the surface of the attached powder to obtain coated powder; the inorganic powder includes SiO2, and the alkaline solution includes NaOH solution. In the step S3, the reaction formula of the reaction between the inorganic powder and the alkaline solution is: SiO2+2NaOH=Na2SiO3+H2O.
2. The powder coating method according to claim 1, characterized in that: In step S1, the mesh ratio of the alloy powder is: -100 mesh to +150 mesh accounts for 10-40%, -150 mesh to +200 mesh accounts for 20-70%, and -200 mesh to +400 mesh accounts for 10-30%; the mesh number of the inorganic powder is set to be above 8000 mesh.
3. The powder coating method according to claim 1, characterized in that: In step S3, a binder is added to the attached powder after sufficient reaction with the alkaline solution and the powder is stirred until it is uniformly dried.
4. The powder coating method according to claim 3, characterized in that: The binder is an inorganic binder or an organic binder.
5. The powder coating method according to claim 3, characterized in that: The adhesive is silicone resin, water glass or epoxy resin, and the added amount of the adhesive is 0.2-2.5%.
6. The powder coating method according to any one of claims 1 to 5, characterized in that: In step S1, the alloy powder comprises Fe (100-x-y-z-a-b) Si x B y C z M a N b , where M is any one of Ni and Mo elements, and N is any one of Cr and Mn elements; where 6﹤x﹤11, 9﹤y﹤16, 1﹤z﹤8, 0≤a﹤5, 0﹤b﹤5.
7. The powder coating method according to claim 6, characterized in that: The alloy powder comprises Fe 76 Si 7.5 B7C4 1.5 Cr3, its performance is reflected in the Bs of the amorphous strip prepared with this composition is 1.54T, Hc is 1.7A / m, μi @1k,0.5V is 21400; or its composition includes Fe 75 Si8B7C4Mo1Cr5, the performance of the amorphous strip prepared with this composition is shown in that Bs is 1.33T, Hc is 1.2A / m, and μi @1k,0.5V is 38600; or its composition includes Fe 78 Si6B8C3Ni3Mn2, the performance of the amorphous strip prepared with this composition is shown in that Bs is 1.71T, Hc is 3.6A / m, and μi @1k,0.5V is 8400; or its composition includes Fe 76 Si9B7C5Cr3, the performance of the amorphous strip prepared with this composition is shown in that Bs is 1.42T, Hc is 1.5A / m, and μi @1k,0.5V is 28500; or its composition includes Fe 78 The performance of Si6B9C4Cr3 is reflected in the fact that the Bs of the amorphous strip prepared with this composition is 1.51T, the Hc is 2.2A / m, and the μi @1k,0.5V is 13600.
8. A method for preparing a finished powder, using the powder coating method according to any one of claims 1 to 7; characterized in that: The following steps are also included: S4. Add a lubricant to the obtained coated powder, and stir and mix it with a stirrer to obtain a finished powder.
9. A method for preparing a finished magnetic powder core, using the method for preparing a finished powder core as claimed in claim 8; characterized in that: The following steps are also included: S5, treating, sintering, annealing and curing the obtained finished powder to obtain a magnetic powder core base block; S6. Performing surface coating treatment on the magnetic powder core base block to obtain a finished magnetic powder core.
Citation Information
Patent Citations
Preparation method of mu90 high-permeability Fe-based amorphous magnetic powder core
CN103219119A
Soft magnetic amorphous alloy
JP2009120927A